POST-SCHOOL OUTCOMES OF STUDENTS WITH SPECIAL EDUCATIONAL NEEDS IN HONG KONG: A QUALITATIVE INVESTIGATION OF TEACHERS’ OBSERVATIONS (Proceedings of International Conference on Special Education, 2015)
To help students with special educational needs (SEN) to achieve smooth transitions from secondary school to higher education, to post-school employment and other outcomes that suit their development needs is one of the core goals of special education. It is also a key component of worldwide practices of inclusive education. Making an effort to contribute to research and practical development in this area in Asian regions, the present study examined post-school outcomes of SEN students in a Hong Kong setting. A qualitative approach was used by conducting a series of focus group interviews to teachers. Together with our findings of teachers’ relatively rich observations of post-school outcomes for SEN students and transition difficulties usually encountered by this group of students, a dilemma also emerged from teachers’ perceptions and observations of SEN students and their parents’ expectations to postschool outcomes and realistic outcomes they could achieve. Implications and future directions are discussed.